Public Health and Hepatitis C - Patrick, David M. (Can J Public Health, 2000)
This paper reviews key public health aspects related to surveillance, transmission and primary prevention of hepatitis C. Hepatitis C is now a reportable disease in all Canadian provinces and territories. Although prevalence in Canada is estimated at under 1%, that associated with injection drug use (IDU) approaches 90%. The epidemiology of new HCV infections in Canada is now primarily defined by IDU behaviour, with annual incidence rates among new drug injectors exceeding 25%. HCV is less efficiently transmitted through other routes of exposure. An effective vaccine against HCV remains elusive. Some jurisdictions offer hepatitis A and hepatitis B vaccine to HCV-infected persons. An array of harm reduction strategies targeting IDU has been implemented but underdeployed across Canada, and has been ineffective to date in controlling the HCV epidemic. Public policy alternatives, such as legalization and regulation of injection drugs, are being debated. Improved HCV preventive strategies are urgently required and need careful evaluation. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/BF03405102 and is accessible for authorized users.